Argumentação e prova no estudo de progressões aritméticas com o auxílio do Hot Potatoes - Solis, Alexandre (2008)
This research work deals with the theme Argumentation and Proof in the study of Arithmetic Progressions. Its purpose is to investigate the cognitive development of students in building concepts and knowledge related to the Numerical Sequence and Arithmetic Progression (AP), and in developing argumentation and proof-related competencies. Such purposes resulted from the experience in meetings with the research group of the project Argumentation and Proof in School Mathematics (AProvaME) at Pontifícia Universidade Católica de São Paulo (PUC/SP). As research methodology, there were used some principles of Didactical Engineering, and, for developing this work, a sequence of nineteen activities was prepared, which was applied to a group of eight students of the first year of the Brazilian High School Program from a Public School of the State of São Paulo. An authoring software known as Hot Potatoes was used for preparing the nine activities of the sequence. The JCloze tool of this software showed to be proper for the teacher, because it allowed the easy building of activities. As regards the students, it was possible to check the answers given, allowing more autonomy for solving the activities. The trial analyses showed that the sequence of activities permitted students to build concepts related to the Numerical Sequence and Arithmetic Progression, as well as competencies in mathematical argumentation and proof, more specifically, in the development of deductive reasoning that led them to determine the generalization of numerical sequences and to deduct the General Term Formula for AP. This research had a significant impact on my education and my understanding about the importance of argumentation and proof in the teaching practice